2020
DOI: 10.1016/j.cognition.2020.104200
|View full text |Cite
|
Sign up to set email alerts
|

Does short-term memory develop?

Abstract: Such is the consistency by which performance on measures of short-term memory (STM) increase with age that developmental increases in STM capacity are largely accepted as fact.However, our analysis of a robust but almost ignored findingthat span for digit sequences (the traditional measure of STM) increases at a far greater rate than span for other verbal materialfundamentally undermines the assumption that increased performance in STM tasks is underpinned by developmental increases in capacity. We show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 61 publications
3
15
3
Order By: Relevance
“…Thus, meaning does not seem to be necessary for the effect. Jones and Farrell (2018) further demonstrated that people are more likely to recall sentence-like lists in an order consistent with syntactic knowledge and that errors are more likely to conform to prior syntactic knowledge than expected by chance (for corpus analyses tying language experience to memory performance, see Perham et al, 2009;Jones et al, 2020). In each case, inter-item information affected memory for order via long-term knowledge of language syntax, suggesting that memory for items and their order interact to support each other.…”
Section: Separated Representations In Memory-modelsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, meaning does not seem to be necessary for the effect. Jones and Farrell (2018) further demonstrated that people are more likely to recall sentence-like lists in an order consistent with syntactic knowledge and that errors are more likely to conform to prior syntactic knowledge than expected by chance (for corpus analyses tying language experience to memory performance, see Perham et al, 2009;Jones et al, 2020). In each case, inter-item information affected memory for order via long-term knowledge of language syntax, suggesting that memory for items and their order interact to support each other.…”
Section: Separated Representations In Memory-modelsmentioning
confidence: 97%
“…Whereas some researchers have considered poor VWM performance as a cause of poor language skills, potentially ameliorated by working memory training (e.g., Ingvalson et al, 2015), our language-emergent VWM view suggests that poor VWM performance is a symptom associated with poor language skill. In other words, the abilities to encode, maintain, and order verbal information are skills that emerge from language use, and individuals who have higher language skills have richer LTM representations and more practiced comprehension and production processes (see also Jones et al, 2020). Thus, we can view tasks that are described as VWM tasks not as assessments of a separate VWM capacity but rather as measures of a person's skill in encoding and maintaining verbal information.…”
Section: Implications For Relating Wm Assessments To Other Measuresmentioning
confidence: 99%
“…The challenge for mechanistic accounts arguing that apparent working memory capacity limitations are the consequence of shortfalls in long-term language knowledge is, of course, to explain how and why speech encoding is deficient without appealing to a primary working memory capacity bottleneck. Along these lines, computational modelling of variance in non-word repetition and span task performance among typically developing individuals has appealed to the notions of input frequency and regularity (Jones, 2016;Jones et al, 2007Jones et al, , 2008Jones et al, , 2020MacDonald & Christiansen, 2002;Jones et al, 2020;MacDonald & Christiansen, 2002). Here, the idea is that the ability of an artificial neural network to accurately process any given speech sequence relates directly to the quality of the network's established, analogous representations, which is higher when the relevant input previously received is frequent and structurally consistent.…”
Section: Rethinking Working Memory Capacity Deficits In Dldmentioning
confidence: 99%
“…This indicates that a separate buffer system which hypothetically varies in capacity between individuals (e.g., a phonological loop) is not required to explain variance in task performance; variance in the frequency of stimulus exposure and therefore the quality of long-term encodings (i.e., more frequently encountered, regular stimuli are better encoded) can parsimoniously account for the data at hand. The long-term encoding benefits of high frequency and regularity of exposure clearly boost performance for certain stimuli in working memory tasks, and may more broadly explain why working memory capacity appears to increase during infancy and childhood (Jones et al, 2020). Simply, as implicit in the state-based framework of working memory, task performance may improve as children become increasingly adept at deploying their mounting long-term language knowledge in the moment, not, as is commonly argued, because of developmental capacity increases that are independent of the quality of long-term representations (Gathercole et al, 2004).…”
Section: Rethinking Working Memory Capacity Deficits In Dldmentioning
confidence: 99%
“…They review evidence for non-word repetition performance being linked to knowledge of phonological patterns and vocabulary, and they argue that non-word repetition tests measure the quantity and quality of language skill and experience relevant to the specific demands of this particular task, rather than a separate memory capacity. Similarly to G. Jones et al’s (2020) argument for span tasks, Schwering and MacDonald (2020) argue that what non-word repetition tests measure is language ability.…”
mentioning
confidence: 98%